Three-dimensional inkjet printing of electrically active materials - Nelson-Dummett, O.B. (2025)
Additive Manufacturing (AM) for electronics (AME) offers the capability for a new generation of devices, with digitised customisation, remarkable design freedom, and low wastage. To achieve this, AM must enable excellent material properties, high resolution, multi-material processing, and scalability to attain industrial relevance. Inkjet printing (IJP) is one of the most mature technologies capable of such material properties and resolution, originating from graphical printing but now with several decades of research into functional materials behind it. IJP excels at multi-material processing and scalability, but major criticisms are the high anisotropy and inability to print truly 3D geometries, generally settling on 2.5D heterostructures instead.